1985
DOI: 10.1289/ehp.8564209
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical chemistry of sulfite.

Abstract: The free-radical chemistry of sulfite oxidation is reviewed. Chemical transformations of organic and biological molecules induced by sulfite oxidation are summarized. The kinetics of the free-radical oxidations of sulfite are discussed, as are the kinetics of the reactions of the sulfite-derived radicals A03 and the peroxy derivative S(6 with organic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
158
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(162 citation statements)
references
References 80 publications
(70 reference statements)
4
158
0
Order By: Relevance
“…Sulfur dioxide, one of the major atmospheric pollutants, is water-soluble and, in aqueous solution at neutral pH, exists primarily as sulfite (SO 3 2− ) and (bi)sulfite (HSO 3 − ) (pKa = 7.2) [15]. Due to its antioxidant and antimicrobial properties, (bi)sulfite is used extensively as a preservative in beverages and foods [6], but it has also been reported that (bi)sulfite is toxic at high concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur dioxide, one of the major atmospheric pollutants, is water-soluble and, in aqueous solution at neutral pH, exists primarily as sulfite (SO 3 2− ) and (bi)sulfite (HSO 3 − ) (pKa = 7.2) [15]. Due to its antioxidant and antimicrobial properties, (bi)sulfite is used extensively as a preservative in beverages and foods [6], but it has also been reported that (bi)sulfite is toxic at high concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…This metal-catalyzed autoxidation generates sulfur trioxide anion radical ( • SO 3 − ) in an initiating one-electron oxidation step through an oxygen-consuming chain reaction [3,5,10,11]. It has also been shown that the one-electron oxidation of (bi)sulfite to sulfate is catalyzed enzymatically by prostaglandin H synthase (hydroperoxide) [12], horseradish peroxidase [13,14] and xanthine oxidase [15–17] with formation of • SO 3 − .…”
Section: Introductionmentioning
confidence: 99%
“…SO 5 -radicals. Direct evidence of the radicals' presence during the course of the reaction has been often described, e.g., in [14,15]. A more detailed overview of possible reactions taking part in the mechanism and covering almost all sulfur-oxygen compounds was given by Ermakov and Purmal [8].…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…In healthy individuals beside enzymatic transformation other processes to control the level of sulfite must be involved: for instance, chemical pathways. In fact, the sulfite reacts with disulfide proteins bond such as oxidized glutathione and cystine leading to the formation of the corresponding sulfidryl derivative, or is oxidized to sulfate [4] [5]. But, the mechanism of both the negative and positive actions in which the sulfite could be involved is not clear; for example, it has been suggested that the sulfite might affect some mediators such as the nitric oxide and/or its carriers [6]- [8].…”
Section: Introductionmentioning
confidence: 99%